Reconsidering Intellectual Disability : L'Arche, Medical Ethics, and Christian Friendship - Greig, Jason Reimer (Book collections on Project MUSE., 2015)
In 2004, the parents of Ashley, a young girl with profound intellectual disabilities, chose to stop her growth, perform a hysterectomy, and remove her breast buds. This "Ashley Treatment" (AT) was performed in consultation with pediatric specialists and the hospital ethics committee, who reasoned that these changes would improve Ashley's quality of life and ease the burden on her primary caregivers: her mother and father. But Jason Reimer Greig proposes that the AT represents the most pernicious elements of modern medicine in which those with intellectual disabilities are seen as objects and perpetual children in need of technological manipulations. Drawing on--and criticizing--contemporary disability theory, Greig contends that L'Arche, a federation of Christian communities serving the intellectually disabled, provides an alternative response to the predominant bioethical worldview that sees disability as a problem to be solved. Rather, L'Arche draws inspiration from Jesus' service to the "least of these" and a commitment to Christian friendship between the able-bodied and the intellectually disabled, in which the latter are understood not as objects to be fixed but as teachers whose lives can transform others into a new way of being human